(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Silver nanoparticles was reflected a powerful antimicrobial agents newly exclusively after growing incidence of diseases related with biofilm and multi-drug resistant pathogens which essential required to find a different path to eliminate that‘s challenge. So the aim of present study was to synthesize silver nanoparticles through biological method using bacteria Eschriesca coli . Biological silver nanoparticles were described by several techniques. The UV-visible spectrophotometric indicated absorbance peak at 246 to 356 nm, Fourier Transformer Infrared analysis (FTIR) revealed that carboxylic groups and poly phenolic groups are enclosed on the surface of both silver nanoparticles creating stabilized nanoparticles, and by scanning electron microscope (SEM), which shown that the biosynthesized silver nanoparticles were spherical in size 26.22 to 31.44 nm. Optimization of silver nanoparticle biosynthesis by E. coli was performed for parameters (temperature and pH and concentration of silver nitrate solution) and the results discovered that temperature 60°C , pH 7 and 3 M silver nitrate concentration were the optimum conditions for silver Nano particles biosynthesis by E. coli isolated from clinical samples of Thi -Qar (Nassryah) city-south Iraq.